ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN TRANSFER PRICING PADA PERUSAHAAN DI INDONESIA - Dina Afriana, - (2019)
This paper aims to determine the effect of Tax, Firm Size, Tunneling Incentives on Transfer Pricing on non-financial companies listed in Indonesia Stock Exchange period 2013-2017. The sampling in this study of 11 non-financial companies listed in Indonesia Stock Exchange period 2013-2017 with purposive sampling method. The analysis technique used is multiple linear regression which is processed through the Stastistical Product and Service (SPSS) Software with a significance level of 5%. The limitations of this study is there are many outliers that make data deviation far from the average, thereby reducing many research samples and transfer pricing measurements only come from related party receivable from sales and loan. The results in this study indicates that Tax has significant effect on Transfer Pricing, Firm Size has no significant effect on Transfer Pricing, and Tunneling Incentives has no significant effect on Transfer Pricing.